Fabrication of Biocompatible, Functional, and Transparent Hybrid Films Based on Silk Fibroin and Epoxy Silane for Biophotonics - Silva, Robson R. da [UNESP]; Cavicchioli, Mauricio [UNESP]; Lima, Lais R. [UNESP]; Otoni, Caio G.; Barud, Hernane S.; Santagneli, Silvia H. [UNESP]; Tercjak, Agnieszka; Amaral, Andre C.; Carvalho, Renata A.; Ribeiro, Sidney J. L. [UNESP] (Amer Chemical Soc, 2017)
In this work we explored the fabrication of flexible and transparent hybrids of silk fibroin (SF) and epoxy modified siloicane for photonic applications. It is well-known that regenerated SF solutions can form free-standing films with high transparency. Although SF has a restricted number of chemically reactive side groups, the main issues of as-cast pristine SF arts regard the high solubility into aqueous media, brittleness, and low thermal. stability. The design of SF films with enhanced functionality but high transparency triggers new opportunities on a broader range of applications in biophotonicS. Here we present a simple, functional, yet remarkably versatile hybrid material derived from silica sol, gel process based on. SF protein and (3-glycidyloxypropyl) trimethoxysilane (GPTMS), an organically modified Silicon-alkoxide owning a reactive terminal epoxy group: Specifically, we investigated the effect of the addition of GPTMS into SF solutions on the processability, morphology, crystallinity, and mechanical and optical properties of the resulting hybrid films. Highly transparent (ca. 90%); and flexible free-standing hybrid films were achieved. Cell viability assays revealed that the hybrid films are noncytotoxic to rat osteoblast cells even at :high GPTMS content (up to 70 wt %). The hybrid films showed enhanced thermal stability and were rich in organic (epoxy) and inorganic (silanol) functional groups according to the content of GPTMS. We also evaluated the successful preparation of high qualify optical red emissive SF hybrid films by loading YVO4:Eu3+ nanoparticles at low concentration (<5 wt %). A meaningful description of the hybrid filth structure is reported from the combination of scanning electron and atomic force micrOscopies, vibrational spectroscopy, solid-state NMR, and X-ray diffraction analyses.
Keywords: photonics; hybrids; silk fibroin; GLYMO; glycidyl 3-(trimethoxysityl)propyl ether